Selective photocatalytic hydroxylation and epoxidation reactions by an iron complex using water as the oxygen source. Issue 11 (22nd September 2017) - Chandra, Bittu; Singh, Kundan K.; Gupta, Sayam Sen
Abstract : Iron complex catalysed selective and efficient photocatalytic hydroxylation and epoxidation reactions using water as the oxygen atom source has been reported. Abstract : The iron complex [(bTAML)Fe III –OH2 ] − (1 ) selectively catalyses the photocatalytic hydroxylation and epoxidation reactions of alkanes and alkenes, respectively, using water as the oxygen-atom source. Upon the oxidation of unactivated alkanes, which included several substrates including natural products, hydroxylation was observed mostly at the 3° C–H bonds with 3° : 2° selectivity up to ∼100 : 1. When alkenes were used as the substrates, epoxides were predominantly formed with high yields. In the presence of H2 18 O, more than 90% of the 18 O-labelled oxygen atoms were incorporated into the hydroxylated and epoxide product indicating that water was the primary oxygen source. Mechanistic studies indicate the formation of an active [{(bTAML)Fe IV }2 -μ-oxo] 2− (2 ) dimer from the starting complex1 via PCET. The subsequent disproportionation of2 upon addition of substrate, leading to the formation of Fe V (O), renders the high selectivity observed in these reactions.